Peran Remodeling Atrium pada Fibrilasi Atrium - Ignatius Yansen; Muhammad Munawar (Jurnal Kardiologi Indonesia, 2011)
Atrial fibrillation (AF) is the most common arrhytmia. AF usually found at older age. AF means greater complication with higher morbidity and mor-talitiy. AF tends to be more frequent and severe. Patients with AF usually very difficult to maintain sinus rhytm after cardioversion. This phenom-enon shows that AF tends to be more severe after time. Atrial fibrillation can influence the condition in atrium so the atrium tends the withold the arryhtmia condition. Changes in atrium induced by atrial fibrillation that starts atrial fibrillation called atrial remodelling. This phenomenon is called AF begets AF. Respons can be miocyt growth, hyperthrophy, necrosis, and apoptosis, the disturbance of extracellular matrix composition, changes in the expression of ion channel, atrial hormon and return to fetal gen programe. These changes causing cascade of reaction that makes atrial remodelling with structural, functional and electrical effect.